Healthy life styles, sleep and fatigue in endometrial cancer survivors: A cross‐sectional study. Issue 7 (7th February 2020) - Yu, Chia‐Hui; Wang, Tsae‐Jyy; Chang, Chih‐Long; Liang, Shu‐Yuan; Wu, Shu‐Fang; Liu, Chieh‐Yu; Lu, Yu Ying
Abstract: Aims and objectives: The primary aim of this study is to explore the influence of obesity, healthy lifestyle and sleep quality of endometrial cancer survivors on their fatigue level. Background: As many as 30% of endometrial cancer survivors still suffer from fatigue 5 years after completing therapy. Fatigue may hinder cancer survivors from participating in daily activities or returning to their original roles and functions, thus affecting their health‐related quality of life. Design: This study adopted a cross‐sectional correlational research design. The STROBE checklist for cross‐sectional studies was used as a reference for reporting the study. Methods: A consecutive sample of 134 endometrial cancer survivors was recruited from the outpatient clinics of a medical centre in Taipei, Taiwan. Data were collected using structured questionnaires. Results: Study subjects scored 44 points ( SD = 7.09) on average for the fatigue levels. Results of linear regression showed that sleep quality ( ß = −0.38), comorbidity index ( ß = −0.024) and age ( ß = 0.20) were important predictors of fatigue. However, differences in obesity, vegetable and fruit intake, physical activity did not lead to significant differences in fatigue level. Conclusions: Survivors who had poorer sleep quality, higher comorbidity index and younger age reported higher fatigue. Relevance to clinical practice: The study findings are relevant for assessing and preventing fatigue in endometrial cancer survivors. Those with poorer sleep quality, higher comorbidity index and younger age are at a greater risk for fatigue and deserve further attention. Although the study results failed to support the link between obesity, vegetable and fruit intake, physical activity and fatigue, the ratio of survivors who comply with recommended healthy lifestyles was low. Hence, it is of urgent necessity that this population receives the help to maintain a healthy lifestyle.